Effect of Workload on Mental Health and Performance in Nutrition Installations - Stefani, Shiela; Kosasih, Kosasih (Asosiasi Ide Bahasa Kepri, 2024)
This theoretical research analyzes the relationship between workload and the performance and mental health of health workers, with a focus on effective workload management strategies. This study examines theoretical models, such as the Job-Demands Resources Model and the Effort-Recovery Model, to understand how the workload dimensions—physical, mental, and temporal—affect the well-being and productivity of healthcare workers. This study emphasizes the importance of balanced workload distribution, adequate social support, and flexible time management to reduce stress, prevent burnout, and improve work performance. This theoretical discussion is relevant for health workers in general, but the specific implications are directed to nutrition installation staff in hospitals who often face heavy physical and mental tasks. If not managed properly, workload can reduce the efficiency and quality of services as an indirect effect of poor mental health and performance. Therefore, this study emphasizes the urgency of implementing effective workload management strategies to support mental health and performance of healthcare workers in a stressful work environment